(3ehdO GdfHj Udi Gddg Ydjg hSde GdYQhSs - (3GdbQTj GdJjej GdHcQj GdMfHdj, CHh GdaQL, GHf GdLhRj, LeGd GdOjf, YHO GdQMef Hf Ydj Hf eMeO, (B597 (3g`s ((3UGdM GdcGTas)
(3ChdgG (B:s
(3GdMeO ddg GdPj CHQR ef ZQI YQhS GdMVQI UHMG eSJfjQG hCWdY aj CadGc GdceGd ef HQhL GdLeGd TeSG hbeQG eSJfjQG hGNJGQ aj GdbOe SjO Gdchfjf MHjHGs
(3BNQgG (B:s
(3hWjH GdfTQ aj GdCchGf aGFM haj ChUGag JJdi GdeOGFM hCfRd ajg BjGJ cQjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3 / 316s
(3eYLe GdeDdajf(B: (3L(B2 / 100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs